Higher Education and Innovation Design of an Innovative Teaching Module for an Intensive Programme on Aeolian Architecture - Sapienza, Vincenzo; Voica, Marius; Finocchiaro, Luca (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book highlights the design of an educational module for an innovative intensive program. The theme is very relevant in the contemporary approach to teaching activities. In fact, thanks to the didactic design, it is possible to obtain a strong relationship between teachers and learners, as required by the Bologna Process. It also allows a stronger definition of learning outcomes. After a general excursus on the subject, the manuscript refers to a recent experience carried out in the Aeolian Island for the Erasmus + Programme, called VVITA. In it, an international group of students and teachers spent a period in the Aeolian Islands, to focus on the features of local vernacular architecture. The attention has been addressed to the Aeolian House, which is a wonderful example of ante litteram sustainable architecture. On the island of Filicudi, one of the most beautiful of the archipelago, it has preserved its characteristics intact. The book is completed by teachers' lectures and students' final reports.